The Analysis of 4-C in Moodle-Based Online Learning in Science Learning Media Courses - Desak Made Anggraeni; Ferdinandus Bele Sole (Postgraduate, University of Mataram, 2022)
This study aims to describe the 4-C competencies in moodle-based online learning. This type of research is descriptive qualitative research. This research was conducted at STKIP Weetebula, Southwest Sumba district. The object of this research is the students of the sixth semester of the elementary school teacher education study program (PGSD), a total of 90 people. The time of this research is from February to May 2022. The data collection technique used is a documentation study. The data analysis technique in this study uses the data analysis technique of the Miles and Huberman model, namely data analysis that is carried out directly and continuously until it is complete, so that the data is saturated. The steps in this data analysis are: Data Reduction, Data Display (data presentation) and drawing conclusions. Based on the research results, it can be concluded that online learning based on moodle can develop 21st century competencies in the form of critical thinking & problem solving; collaboration; communication; creative thinking & innovation